The learner between cultures: interculturality and interpreting teaching in China - Jatobá, Júlio Reis (BELT - Brazilian English Language Teaching Journal, 2019)
This article is a reflection on the teaching of Chinese-Portuguese Interpreting in China. The point of our discussion will be: if the foreign language teaching can serve as bridges or walls of intercultural communication (see Gao, 1995), what is the space of the target language culture and the intercultural discussion in the Interpreting classes for PFL students? In this article we will defend the need of the teaching of Interpreting for PFL Chinese learners to be rethought as a fertile space for the (re) creation, discussion, and production of meanings that amplify and produce positive and inclusive attitudes towards the improvement of mutual understanding and communication between the universes of Portuguese-speaking countries and the universes of Chinese languages and cultures. To do so, we will base on and compare our discussion with the results of the two studies. The first discusses the real practices of Interpreting and their implications in the teaching/learning process of PFL in China (Jatobá, 2015) and the second regards to linguistic ideologies and individual differences in PFL contexts in China (Jatobá, 2014).